Pengaruh Profitabilitas Dan Leverage Terhadap Pengungkapan Sustainability Report pada Laporan Keuangan Perusahaan Yang Terdaftar Pada BEI Tahun 2019 - 2024: (Studi Kasus Pada Sektor Perusahaan Manufaktur Semen) - Umi Mas'ulah; Iip Dyah Kusumaningati; Syariful Anam (PT. Karya Inovatif Nusantara, 2026)
Sustainability report disclosure drives continuous improvement in company operations. This study aims to determine the effect of profitability and leverage on sustainability report disclosure in the financial statements of cement manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2019-2024 period. The research method used a quantitative descriptive approach. The population used was five cement manufacturing companies listed on the IDX for the 2019-2024 period. The sampling technique used probability sampling, resulting in a sample of 30 sustainability report and annual report data from cement manufacturing companies. The results show that profitability (ROE) has no significant partial effect on sustainability report disclosure, as evidenced by a t-test result of 0.590 > 0.05. Leverage (DER) has a significant partial effect on sustainability report disclosure, as evidenced by a t-test result of 0.002 < 0.05. The f-test result of 0.009 < 0.05 indicates that profitability and leverage simultaneously influence sustainability report disclosure. Further research is expected to use other variables that have an influence on sustainability report disclosure so that the results obtained are more influential.